2012
DOI: 10.1002/j.2161-1882.2012.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attachment, Cognitive Appraisal, and University Students' Reactions to Romantic Infidelity

Abstract: This study examined the relationships between adult attachment, cognitive appraisal, and university students' behavioral and emotional reactions to infidelity situations in romantic relationships. Results based on 173 university students suggested that both attachment and cognitive appraisals significantly predicted distinct types of infidelity reactions and that participants' cognitive appraisal mediated the effects of attachment on behavioral and emotional reactions. Counseling applications for university co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…Considerando-se que o MIO tende a guiar afetos e comportamentos específicos durante interações com figuras de apego (Bowlby, 1979) e levando-se em conta que o parceiro amoroso se torna a figura de apego na vida adulta, estudos têm demonstrado relação entre estratégias de resolução de conflitos e estilos de apego. O estilo de apego influencia a regulação do afeto predominante diante de eventos estressantes, tais como as situações conflitivas (Wang, King, & Debernardi, 2012). Assim, pesquisas indicam que o apego seguro está associado a estratégias de comunicação positiva entre maridos e esposas (Salvatore, Kuo, Steele, Simpson, & Collins, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Considerando-se que o MIO tende a guiar afetos e comportamentos específicos durante interações com figuras de apego (Bowlby, 1979) e levando-se em conta que o parceiro amoroso se torna a figura de apego na vida adulta, estudos têm demonstrado relação entre estratégias de resolução de conflitos e estilos de apego. O estilo de apego influencia a regulação do afeto predominante diante de eventos estressantes, tais como as situações conflitivas (Wang, King, & Debernardi, 2012). Assim, pesquisas indicam que o apego seguro está associado a estratégias de comunicação positiva entre maridos e esposas (Salvatore, Kuo, Steele, Simpson, & Collins, 2011).…”
Section: Introductionunclassified
“…Marchand (2004) comprovou maior frequência de conflito em homens com apego inseguro comparativamente àqueles com um apego seguro. Além disso, indivíduos com apego ansioso tendem a ter um autoconceito negativo e são mais suscetíveis a responder a uma situação de ameaça com emoções exageradas e com medo de perder o parceiro (Wang et al, 2012), experimentando e expressando sentimentos mais intensos de mágoa durante episódios de conflito (Overall, Girme, Lemay Jr, & Hammond, 2014). Ademais, usam menos as habilidades de construção de solução de problemas e o estilo positivo de comunicação (Bogda & Sendil, 2012).…”
Section: Introductionunclassified
“…Dewitte et al (2010) also found that attachment security was related to weaker cortisol responses and less withdrawal behaviors to signs of partner's rejection. More secure people tend to report lower levels of jealousy, suspicion, and worries about relationship exclusivity as compared to less secure people and to experience lower levels of fear, guilt, shame, sadness, inferiority, and anger (e.g., Donovan & Emmers-Sommer, 2012;Guerrero, 1998;Marazziti et al, 2010;Radecki-Bush et al, 1993;Wang, King, & Debernardi, 2012). More secure people tend to report lower levels of jealousy, suspicion, and worries about relationship exclusivity as compared to less secure people and to experience lower levels of fear, guilt, shame, sadness, inferiority, and anger (e.g., Donovan & Emmers-Sommer, 2012;Guerrero, 1998;Marazziti et al, 2010;Radecki-Bush et al, 1993;Wang, King, & Debernardi, 2012).…”
Section: Responses To a Partner's Negative Behaviorsmentioning
confidence: 99%
“…On the other hand, when a man cheats on his partner emotionally, the woman partner also thinks that sexual infidelity has happened as well (Wilson et al 2011). Beyond gender and the type of infidelity, according to Wang et al (2012), reactions to romantic infidelity differ; some people, who are constructive, try to solve the problems in their relationship, some people, who are passive, try to deny or avoid the situation, and some people behave revengefully, that is, they try to take a revenge or behave aggressively.…”
Section: Introductionmentioning
confidence: 99%
“…Several variables may impact how people react to infidelity and how they cope with it such as the discovery method of the infidelity (Afifi et al 2001), and cognitive appraisal (Wang et al 2012). The present study focuses on ruminative tendencies and its two subtypes called brooding and reflection.…”
Section: Introductionmentioning
confidence: 99%